2017
DOI: 10.1186/s12913-017-2679-0
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for prioritization of HIV programs in Viet Nam: a discrete choice experiment

Abstract: BackgroundWith the decline in funding for Viet Nam’s response to the HIV epidemic, there is a need for evidence on the criteria to guide the prioritization of HIV programs. There is a gap in the research on the relative importance of multiple criteria for prioritizing a package of interventions. This study elicits preferences and the trade-offs made between different HIV programs by relevant stakeholders and decision-makers in Viet Nam. It also pays attention to how differences in social and professional chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…First, to examine which attributes were used in previous DCEs on patients' preferences in HIV treatment, a literature review was conducted in PubMed [11][12][13][14][15][16][17] . This was aided by a previous best-worst scaling study 18 , which identified the most important treatment characteristics of HIV patients in Colombia.…”
Section: Attributes and Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, to examine which attributes were used in previous DCEs on patients' preferences in HIV treatment, a literature review was conducted in PubMed [11][12][13][14][15][16][17] . This was aided by a previous best-worst scaling study 18 , which identified the most important treatment characteristics of HIV patients in Colombia.…”
Section: Attributes and Levelsmentioning
confidence: 99%
“…those patients prefer a large positive effect on life expectancy, and low levels of side effects). These expectations were based on intuitive assumptions and existing studies [11][12][13][14][15][16][17] .…”
Section: Questionnairementioning
confidence: 99%
“…In the United Kingdom, preferences for shorter appointment waiting times, longer opening hours, and the type of HIV care provider (general practitioner vs HIV clinic) were prioritized [14], while flexible medical and psychosocial support were priority features according to policy makers and PLWH in Thailand [70]. Three studies specifically assessed preferences of policy makers regarding HIV program design, identifying preference for prevention interventions [74] among high-risk groups [70] and compared to other non-HIV related public health interventions [69].…”
Section: Resultsmentioning
confidence: 99%
“…17 Multiple indicators have been used to prioritize HIV services; these include burden of the disease, coverage and cost of services. [18][19][20][21] Chavan and colleagues used seven indicators (Total PLHIV, ICTC HIV%, PPTCT HIV%, key population estimates in recent mapping and 2009 estimates for FSWs and MSM) to prioritize districts in Gujarat. 22 Though this was a useful exercise, the parameters were restricted to the existing burden of disease and estimates of key population.…”
Section: Discussionmentioning
confidence: 99%